Upper Level Technical Orientation and First Level Leadership Within a Noncontingency and Contingency Framework - Hunt, James G.; Osborn, R. N.; Larson, Lars L. (Academy of Management Journal, 1975)
When direct relationships were examined between first level manager consideration and work group criteria in three state mental institutions, there were significant findings. Similar tests for initiating structure and influence with superiors and for upper level technical orientation revealed no such relationships. Significant relationships were found within a contingency context, however.